What determines plant species diversity along the Modern Silk Road in the east?. Issue 1 (9th January 2023) - Liu, Yanlei; Xu, Chao; Dong, Wenpan; Chen, Xun; Zhang, Wen; Sun, Yuzhe; Wang, Guohong; Wang, Yufei; Zhou, Shiliang
Abstract: As primary producers, plants provide food, oxygen, and other resources for global ecosystems, and should therefore be given priority in biodiversity protection. Most biodiversity research focuses on biodiversity hotspots, while biodiversity coldspots, such as deserts, are largely ignored. We propose that the factors shaping plant species diversity differ between biodiversity hot spots and cold spots, especially for desert ecosystems. To test this hypothesis, we investigated plant species diversity along the Modern Silk Road in the Northwest China desert, an area characterized by low precipitation, scarce vegetation, a limited number of species, and variable human activities. Surface soil was sampled from 144 plots, environmental DNA (eDNA) was extracted from soil samples, and seed plant species were identified using DNA metabarcoding technology. A total of 671 seed plant species were detected, which was more diverse than indicated by plot survey data. Plant species diversity gradually decreased from east to west along the Silk Road. In this area, temperature determines plant species diversity more than precipitation. Additionally, human activity has altered plant species diversity by introducing crops and invasive plants and eliminating environmentally adapted indigenous plants. Our results demonstrate the potential of eDNA metabarcoding technology for plant species diversity surveying. Desert plants have adapted to dry environments by relying on underground water or utilizing occasional rainfall as ephemerals, which are often not visible during surface surveys because of their short aboveground life cycle but can be detected with eDNA metabarcoding technology. Groundwater maintenance and human activity control are recommended for plant species diversity conservation and desertification control. Abstract : Environmental DNA (eDNA) is a quick and accurate method for biodiversity assessment. This study first used eDNA‐assessed regional plant species diversity. Temperature instead of precipitation is the main factors affecting plant diversity. Human activities were proven to affect plant species diversity in desert areas. More instant plant diversity results need to be done for desertification control. Highlights: Environmental DNA (eDNA) is a quick and accurate method for biodiversity assessment. This study first used eDNA‐assessed regional plant species diversity. Temperature instead of precipitation is the main factors affecting plant diversity. Human activities were proven to affect plant species diversity in desert areas. More instant plant diversity results need to be done for desertification control.